Low-Density Geopolymer Composites for the Construction Industry - Nguyen, Van Vu; Le, Van Su; Louda, Petr; Szczypiński, Michał Marek; Ercoli, Roberto; Růžek, Vojtěch; Łoś, Piotr; Prałat, Karol; Plaskota, Przemysław; Pacyniak, Tadeusz; Buczkowska, Katarzyna Ewa (Polymers, 2022)
The article presents preliminary results in studying reinforced and light-weight geopolymers, which can be employed in buildings, especially for walling. Such materials are very promising for the construction industry having great potential due to their favorable properties such as high mechanical strengths, low thermal conductivity, and low density. Moreover, they also exhibit several advantages from an economic and ecological point of view. The present study exanimated the use of specific fillers for the metakaolin-based light-weight geopolymers, emphasizing the above-mentioned physical properties. This research also investigated the electromagnetic shielding ability of the carbon grid built into the light-weight geopolymer structure. According to the study, the most suitable materials to be used as fillers are polystyrenes, along with hollow ceramic microsphere and Liapor. The polystyrene geopolymer (GPP) achieves five times lower thermal conductivity compared to cement concretes, which means five times lower heat loss by conduction. Furthermore, GPP is 28% lighter than the standard geopolymer composite. Although the achieved flexural strength of GPP is high enough, the compressive strength of GPP is only 12 MPa. This can be seen as a compromise of using polystyrene as a filler. At the same time, the results indicate that Liapor and hollow ceramic microsphere are also suitable fillers. They led to better mechanical strengths of geopolymer composites but also heavier and higher thermal conductivity compared to GPP. The results further show that the carbon grid not only enhances the mechanical performances of the geopolymer composites but also reduces the electromagnetic field. Carbon grids with grid sizes of 10 mm × 15 mm and 21 mm × 21 mm can reduce around 60% of the Wi-Fi emissions when 2 m away from the signal transmitter. Moreover, the Wi-Fi emission was blocked when the signal transmitter was at a distance of 6 m.
Keywords: light-weight geopolymers; polystyrene; carbon fiber grid; walling materials; Liapor; ceramic microsphere